The Effect of Ideology and Resource Advantages on Appeals to the U.S. Supreme Court. (2nd April 2020) - Smith, Andrew H.
Abstract: Scholars examining the relationship between the federal appellate courts and the U.S. Supreme Court have heretofore explored a myriad of explanations for how the Supreme Court determines which cases it will accept for review, including the ideological relationships between the justices and the circuit judges (and courts) and the resource statuses of the petitioning and responding parties. What scholars have overlooked is why some litigants appeal to the Supreme Court at all, given the low rate of review by the Court and the high costs (financial and otherwise) of an appeal. Scholars have also overlooked how changes in these relationships over time, and across circuits, affect the rates of appeals in the aggregate. I hypothesize that greater ideological disagreements between the circuits and the high court increase the rates of appeals over time, and I hypothesize that increases in the resource divide between the "haves" and "have nots" will depress appeals over time.